2017
DOI: 10.1016/j.jana.2017.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Trauma-Informed Decision-Making Among Providers and Victims of Intimate Partner Violence During HIV Testing: A Qualitative Study

Abstract: We explored the process of implementing an HIV testing program at an intimate partner violence (IPV) service agency from the client and provider perspectives. A qualitative descriptive approach was used wherein semi-structured interviews were conducted with 19 key informants (i.e., women with a history of IPV, HIV service providers, IPV service providers). Interviews focused on facilitators and barriers to HIV testing implementation, the decision-making process during HIV testing, and support needs. All interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Our study is the first to quantitively identify a negative association between IPV and HIV testing in a community sample of predominantly minority women living in low-income urban neighborhoods in the United States. This finding reinforces prior studies underscoring the role of IPV exposure as a barrier against HIV testing among women (Etudo et al, 2017; Williams, Gonzalez-Guarda, & Ilias, 2017). IPV experience in the past year (i.e., physical victimization) showed a negative association with HIV testing history in the past 6 months and a positive association with lifetime substance use, indicating that the SAVA syndemic may also apply to HIV testing history among WIC-enrolled mothers living in neighborhoods with high HIV prevalence.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study is the first to quantitively identify a negative association between IPV and HIV testing in a community sample of predominantly minority women living in low-income urban neighborhoods in the United States. This finding reinforces prior studies underscoring the role of IPV exposure as a barrier against HIV testing among women (Etudo et al, 2017; Williams, Gonzalez-Guarda, & Ilias, 2017). IPV experience in the past year (i.e., physical victimization) showed a negative association with HIV testing history in the past 6 months and a positive association with lifetime substance use, indicating that the SAVA syndemic may also apply to HIV testing history among WIC-enrolled mothers living in neighborhoods with high HIV prevalence.…”
Section: Discussionsupporting
confidence: 89%
“…Together with the literature showing the inverse relationship between IPV exposure and HIV testing history, evidence underscores the importance of reaching out to women with IPV exposure who are likely to have a risk factor for HIV infection to encourage HIV testing (Etudo et al, 2017). A qualitative study also described several combinations of factors that might function as barriers against HIV testing behavior among those with IPV experiences (e.g., potential for re-traumatization, readiness for testing, other competing priorities, and care for children; Williams et al, 2017). In our study, substance use was not associated with HIV testing history in the past 6 months prior to the survey period, although the current sample did not show a high prevalence of illicit drug use which may have impacted findings.…”
Section: Discussionmentioning
confidence: 99%
“…Health care settings can be a good option to integrate sexual violence and HIV prevention services and HIV counseling can be a good opportunity for empowerment and support [13,54,67]. Additionally, antiretroviral providing centers can help with sexual violence prevention and control, as it has been reported that violence is also associated with a lower attendance [8] and lower treatment adherence among HIV positive participants [85].…”
Section: Discussionmentioning
confidence: 99%
“…First, female victims may not have felt that they were psychologically ready to take on the stressful experience of HIV/STI testing. The HIV/STI testing processes can be very stressful for women because they fear the results (Draucker et al, 2015; Williams, Gonzalez-Guarda, & Ilias, 2017). Victims may have decided against exposing themselves to another potential source of trauma at this time.…”
Section: Discussionmentioning
confidence: 99%
“…Given the individual and public health consequences associated with HIV/STIs, it is important to implement strategies to identify, counsel, and treat HIV/STIs in this population. Offering free, rapid, and confidential HIV/STI testing and counseling for victims of IPV appears to be a promising approach, which is supported by both victims and providers (Draucker et al, 2015; Williams et al, 2017). However, less than half of the clients seeking services for IPV requested testing, and an even smaller proportion received one.…”
Section: Discussionmentioning
confidence: 99%